A Stillborn Multiple Organs’ Investigation from a Maternal DENV-4 Infection: Histopathological and Inflammatory Mediators Characterization - Priscila Nunes; Rita Nogueira; Janice Coelho; Francisco Rodrigues; Natália Salomão; Carollina José; Jorge de Carvalho; Kíssila Rabelo; Elzinandes de Azeredo; Rodrigo Basílio-de-Oliveira; Carlos Basílio-de-Oliveira; Flávia dos Santos; et al. (Viruses, 2019)
Dengue virus (DENV) is an emerging virus involved in outbreaks in Brazil. The association between the virus and vertical transmission, with disorders in the placenta, has raised a worldwide concern. On the 29th gestational week, a pregnant woman presented severe complications due to a DENV infection leading to maternal and fetus death. Postmortem analysis of fetal organs demonstrated the presence of DENV using reverse transcriptase polymerase chain reaction (RT-PCR) in the fetal brain and DENV non-structural protein 3 (NS3) staining in placenta and several peripheral fetal tissues, such as the brain, liver, lungs, and spleen. Histological analysis of the placenta and fetal organs revealed different types of tissue abnormalities, which included inflammation, hemorrhage, edema, and necrosis in placenta and tissue disorganization in the fetus, such as spongiform parenchyma, microglial inflammation, steatosis, hyalinose arteriolar, inflammatory cells in the alveolar septa, and disorganization of the lymphoid follicle. Increased cellularity (macrophage, Hofbauer cells and TCD8+ lymphocytes) and up-regulation of inflammatory mediators such as IFN-γ, TNF-α, RANTES/CCL5, MCP1/CCL2, and VEGF/R2 were detected in the liver, lung, spleen, brain, and placenta, supporting placental and fetus peripheral tissues inflammation. Maternal infection leading to the production of those vascular mediators may alter the vascular permeability, facilitating the virus entry and tissue and barrier dysfunction.